Therapeutic Potential of Curcumin in Breast Cancer: From Basic Research to Clinical Applications - Avan, Amir; Hashemzehi, Milad; ShahidSales, Soodabeh; Hassanian, Seyed Mahdi; Joudi Mashhad, Mona; Khazaei, Majid (Reports of Radiotherapy and Oncology, 2015)
Breast cancer is among the most common types of cancer and the second leading cause of cancer-related death in women. Therefore, finding treatments with the highest effectiveness and least side effects is of great importance. Curcuma langa, commonly known as curcumin, has many advantages, including antioxidant, antiinflammatory, anticancer, and wound-healing properties. The anticancer mechanisms include prevention of malignant cell formation, as well as reduction of angiogenesis and tumor growth, as documented in some malignancies, including pancreatic, ovarian, gastric, and colorectal cancers. Recent research has also documented curcumin activities against breast cancer, in particular molecular pathways involved in cell growth, differentiation, apoptosis, and suppression of inflammation. Therefore, the aim of the current review was to study the effects of curcumin on breast cancer. Conflicts of Interest: The authors declare no conflicts of interest.